XIZMATLAR SOHASIDA SUNʼIY INTELLEKTGA ASOSLANGAN MARKETINGNI JORIY ETISH ISTIQBOLLARI (Marketing Journal, 2026)
AbstractThis article examines the theoretical and practical aspects of implementingartificial intelligence (AI)-based marketing systems in the service sector of Uzbekistan. The purpose of the study was to identify the prospects for digital transformation ofCRM systems and the application of AI technologies in service organizations. Theresearch methodology included system analysis, comparative analysis, secondarystatistical data analysis, and synthesis of scientific sources. The findings indicate thatAI-based CRM systems play a significant role in predicting customer behavior,developing personalized marketing offers, and improving service quality. Theconclusion provides scientific and practical recommendations for the phasedimplementation of AI-driven CRM systems in service sector enterprises.Keywords: CRM marketing, artificial intelligence, service sector, digitaltransformation, customer loyalty, marketing automation, Big data analytics, customerexperience, personalization, predictive analytics, chatbot technologies, omnichannelmarketing, customer segmentation, loyalty Programs, conversion Rate, digitalPlatforms, real-Time Marketing.